Analisis Peran Mahkamah Konstitusi dalam Penyelesaian sengketa Pemilu: Tinjauan dari Perspektif Hukum Tata Negara - Ojak Nainggolan; Meli Hertati Gultom; Nicolaos Manalu (Jurnal Syntax Admiration, 2025)
General elections in Indonesia are an important instrument of democracy, but they are often colored by problems such as fraud and violations, so that doubts arise about the results of the votes obtained by presidential and vice presidential candidates. This study aims to analyze the role and authority of the Constitutional Court (MK) in resolving election disputes and identify the obstacles faced by the Constitutional Court in carrying out its functions. The method used is normative legal research with document studies, focusing on the authority of the Constitutional Court and its impact on democracy, using primary legal materials such as the 1945 Constitution and Law No. 7 of 2017 as well as secondary materials such as books and journals. The results of the study show that the Constitutional Court has a crucial role in maintaining democracy in Indonesia through its authority to resolve disputes over election results. The Constitutional Court has the authority to decide disputes over the results of the General Election (PHPU) of the President and Vice President, members of the DPR, DPD, and DPRD. The dispute resolution process at the Constitutional Court is regulated in Law Number 7 of 2017 concerning General Elections, which allows the parties who have the right to submit dispute applications to the Constitutional Court. However, the Constitutional Court also faces various challenges, such as a very high workload, complexity in the evidentiary process, political pressure, and time constraints. Nevertheless, the Constitutional Court remains committed to maintaining integrity and justice to ensure political stability and respect the voice of the people.